Significance of conducting polyaniline based composites for the removal of dyes and heavy metals from aqueous solution and wastewaters - A review. (March 2021) - Senguttuvan, S.; Senthilkumar, P.; Janaki, V.; Kamala-Kannan, S.
Abstract: Dyes and heavy metals pollution have become a major environmental concern worldwide. Various methods, such as advanced oxidation, biodegradation, precipitation, flocculation, ultra filtration, ion-exchange, electro-chemical degradation and coagulation, have been proposed for the removal of dyes and heavy metals from contaminated wastewater. Of these methods, adsorption and detoxification are considered as the most promising and economically viable. Polyaniline-based composites, a material prepared by combining polyaniline with one or more similar or disimilar materials, have been reported as good adsorbents to remove and detoxify different groups of pollutants due to their unique physical and chemical properties. In the last decade, several studies have reported the effective adsorption (∼95%) of dyes and heavy metals onto polyaniline based composites. Furthermore, some polyaniline -composites reduced the adsorbed heavy metals into less toxic state. This review compiles the application of different polyaniline composites for adsorption and/or detoxifcation of dyes and heavy metals and documents composite preparation methods, morphology and properties of the composites, and mechanism of dyes and heavy metals adsorption. Based on the avilabile literature, this review suggests that more studies are warranted to understand the influence of various conditions and experimental variables on dyes and heavy metals removal from wastewater and/or aqueous solution. Highlights: Substrates properties were retained in the polyaniline composites. Dyes and heavy metals were effectively adsorbed onto polyaniline composites. Electrostatic interaction was reported as a major mechanism in dyes and heavy metals adsorption process. Polyaniline composite has several fold high adsorption rate compared with the substrates.